Formal healthcare network path for hospital discharged patients based on their morbidity - Lopes Lima, Melina; Bordin, Danielle; Fernandes Furquim, Renata Cristini; Andreani Cabral, Luciane Patrícia; Muller, Erildo Vicente; Berger Fadel, Cristina (Revista Cuidarte, 2021)
Introduction: Managing information related to multimorbidity in hospital care is crucial for planning strategies to prevent health problems in high-risk patients in order to enable healthcare systems to be organized more efficiently. Objective: To describe the formal healthcare network path for patients with and without multimorbidity in relation to the use of public healthcare networks after discharge. Materials and Methods: A quantitative descriptive cross-sectional study was conducted with primary data from 445 patients admitted to a university hospital in 2018. Data were collected through analysis of medical records and telephone interviews. Results were analyzed by absolute and relative frequency. Results: A flowchart was developed representing the healthcare network locations used by the patient after hospital discharge based on morbidity. It was possible to confirm the existence of a high prevalence of referral (with multimorbidity (WM): 93.52%, without multimorbidity (WOM): 97.71%) and secondary care attendance, low prevalence of referral (WM: 42.45%, WOM: 36.27%) and primary care attendance (WM: 61.29%, WOM: 64.81%). When putting the three levels of healthcare together, low attendance (WM: 17.98% - WOM: 21.89%) was observed in both groups under study. Discussion: Similar attendance at all healthcare network locations is problematic as these are unequal populations and thus, with different needs. Conclusions: It is important to encourage follow-up of patients with multimorbidity in the primary care network, especially in the period after hospital discharge and strengthen the healthcare network. How to cite this article: Lima, Melina Lopes; Bordin, Danielle; Furquim, Renata Cristini Fernandes; Cabral, Luciane Patrícia Andreani; Muller, Erildo Vicente; Fadel, Cristina Berger. Caminho na rede formal de cuidado em saúde de pacientes pós-alta hospitalar segundo multimorbidade. Revista Cuidarte. 2022;13(1):e1279 http://dx.doi.org/10.15649/cuidarte.1279